2016
DOI: 10.18632/oncotarget.12093
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin promotes neutrophil hierarchical chemotaxis via the p38-membrane receptor pathway

Abstract: Neutrophils are the most abundant leukocytes in peripheral blood and play critical a role in bacterial infection, tumor immunity and wound repair. Clarifying the process of neutrophil chemotaxis to target sites of immune activity has been a focus of increased interest within the past decade. In bacterial infectious foci, neutrophils migrate toward the bacterial-derived chemoattractant N-formyl-Met-Leu-Phe (fMLP) and ignore other intermediary chemoattractants to arrive at the area of infection. Using an under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Endotoxin was recently shown to impair neutrophil chemotaxis toward CXCL8 and hence the “prioritization” process of fMLP via a p38‐dependent mechanism. Thus, the elevated levels of p38 phosphorylation found on RC‐treated neutrophils could promote similar signaling inhibitory effects on CXCL8‐induced migration . Cell tracking data corroborates this hypothesis, as seen by changes in directionality to necrotic zones and distance traveled after RC.…”
Section: Discussionsupporting
confidence: 65%
“…Endotoxin was recently shown to impair neutrophil chemotaxis toward CXCL8 and hence the “prioritization” process of fMLP via a p38‐dependent mechanism. Thus, the elevated levels of p38 phosphorylation found on RC‐treated neutrophils could promote similar signaling inhibitory effects on CXCL8‐induced migration . Cell tracking data corroborates this hypothesis, as seen by changes in directionality to necrotic zones and distance traveled after RC.…”
Section: Discussionsupporting
confidence: 65%
“…LPS-triggered activation of p38 MAPKs is a critical signal transduction pathway that modulates various neutrophil functions (28,29). In the present study, we demonstrated that AMP inhibited the phosphorylation of p38 MAPK in LPS-activated neutrophils.…”
Section: Discussionsupporting
confidence: 61%
“…Regarding the chemotaxis of human neutrophils, fMLF-induced migration predominates over CXCL8or LTB 4 -induced chemotactic cues in vitro. 89 This superior potency of fMLF is enhanced in the presence of LPS, which increases FPR1 expression while inducing internalization of CXCR1/2, BLT1 and C5aR1. 90 In contrast to LPS, IL-4 inhibits the expression of FPR1 on neutrophils.…”
Section: C5ar1mentioning
confidence: 99%